A meta food web for invertebrate species collected in a European grassland. Issue 6 (29th March 2019) - Hines, Jes; Giling, Darren P.; Rzanny, Michael; Voigt, Winfried; Meyer, Sebastian T.; Weisser, Wolfgang W.; Eisenhauer, Nico; Ebeling, Anne
Abstract: Patterns of feeding interactions between species are thought to influence the stability of communities and the flux of nutrients and energy through ecosystems. However, surprisingly few well‐resolved food webs allow us to evaluate factors that influence the architecture of species interactions. We constructed a meta food web consisting of 714 invertebrate species collected over 9 years of suction and pitfall sampling campaigns in the Jena Experiment, a long‐term grassland biodiversity experiment located in Jena, Germany. We summarize information on the 51, 496 potential trophic links, which were established using information on diet specificity and species traits that typically constrain feeding interactions (trophic group, body size, and vertical stratification). The list of species identities, traits, and link‐derivation rules will be useful not only for tests of plant diversity effects on food web structure within the Jena Experiment, but also for considering consistent construction of food webs from empirical data, and for comparisons of network structure across ecosystems. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.